2000
DOI: 10.1136/sti.76.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the vaginal discharge algorithm among pregnant and non-pregnant women in Nairobi, Kenya

Abstract: Objective: To evaluate the validity of diVerent algorithms for the diagnosis of gonococcal and chlamydial infections among pregnant and non-pregnant women consulting health services for vaginal discharge in Nairobi, Kenya. Methods: Cross sectional study among 621 women with complaints of vaginal discharge in three city council clinics between April and August 1997. Women were interviewed and examined for symptoms and signs of sexually transmitted infections (STIs). Specimens were obtained for laboratory diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
5
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 18 publications
3
35
5
4
Order By: Relevance
“…Lack of hygiene, promiscuity, non-use of condoms, the existence of genital tract lesions and high-risk practices during sexual intercourse are factors that promote the transmission of STIs and HIV [1] [6] [12] [13]. Our rate of 50.4% is higher than those of Reed [11] in Indonesia and Wang [10] in China, which were 39% and 41% respectively.…”
Section: Prevalence Of Genital Infectionscontrasting
confidence: 41%
See 2 more Smart Citations
“…Lack of hygiene, promiscuity, non-use of condoms, the existence of genital tract lesions and high-risk practices during sexual intercourse are factors that promote the transmission of STIs and HIV [1] [6] [12] [13]. Our rate of 50.4% is higher than those of Reed [11] in Indonesia and Wang [10] in China, which were 39% and 41% respectively.…”
Section: Prevalence Of Genital Infectionscontrasting
confidence: 41%
“…Our rate of 50.4% is higher than those of Reed [11] in Indonesia and Wang [10] in China, which were 39% and 41% respectively. Higher rates were reported by Nguyen [9] in Vietnam and Fonck [1] in Kenya, which were 75.9% and 94%, respectively. Ulcerations in the genital tract increased the risk of HIV infection, and seropositive women developed precancerous cervical lesions more rapidly (CIN2, CIN3) [1] Indeed, the decline in immunity is recognized as a factor favoring opportunistic infections such as genital candidiasis [16] [17].…”
Section: Prevalence Of Genital Infectionsmentioning
confidence: 93%
See 1 more Smart Citation
“…Esta idade é ainda caracterizada não somente por um perí-odo de maior atividade sexual, mas também por uma maior rotatividade de parceiros 2,3,4,12 . Não fosse a maior taxa de uso de preservativos por parte dos adolescentes, conforme demonstrado recentemente pela Pesquisa de Conhecimentos, Atitudes e Práticas relacionadas à DST/AIDS da População Brasileira em 2008 (PCAP-2008), tanto a prevalência de corrimento nesta faixa etária quando suas respectivas RP em relação às demais idades seriam maiores ainda, sobretudo porque o não uso de métodos de barreiras facilita a ocorrência deste tipo de infecção 12,17,18 .…”
Section: Discussionunclassified
“…It has been reported that BV is also associated with poor pregnancy outcomes such as preterm delivery [2]; moreover, several studies have now reported associations between BV and HIV infection [3,4,5]. BV appears to be particularly common in sub-Saharan Africa, where HIV infection is endemic, and it has been reported at high prevalence rates (20-49%) among women presenting with vaginal discharge to STI clinics [6,7,8]. These rates are very much higher than those reported in industrialised countries [9,10].…”
Section: Introductionmentioning
confidence: 99%